Producción científica sobre tuberculosis en Cali - Colombia, 2007-2016 - Pacheco López, Robinson (Universidad Santiago de Cali, 2020)
Tuberculosis is a global public health problem. The program for Tuberculosis control of Cali must adopt one of their fundamental pillars: research and innovation, for which it requires evaluating the literature developed locally about this disease, in order to establish a baseline of scientific production, to be able to create improvement strategies and public health policies in this regard. The objective of this study has been to conduct an inventory of the scientific production on Tuberculosis in Cali, between 2007 and 2016, identifying the research which contributed to the implementation of control and prevention actions. Finished works were sought such as they were based in any area of knowledge in Tuberculosis in different databases, physical repositories of local university libraries, platforms of scientific groups and met with researchers and staff of the municipal and departmental Secretary of Public Health. Ninety four documents were identified, developed by 13 different institutions.